Igrzyska olimpijskie jako instytucja społeczna - Mańkowski, Dobrosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this article I present the Olympic Games as a social institution that creates and reproduces certain patterns and rules of behavior. I propose a definition of a social institution in the context of the Olympic Games. The Olympic institution imposes the framework for the action of social actors (collective and individual). In addition, the olympic institution co-operates in five fields (five contexts): social, economic, political, cultural and communicative. This article shows the links of selected contexts to the Olympic Games. I refer to the concept of strategic action field and its placement in the institutional field system proposed by Neil Fligstein and Doug McAdam.